The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5539/jel.v8n1p74
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions on Factors Influence Adoption of Formative Assessment

Abstract: Even though teachers has positive attitude towards formative assessment, their perceptions on factors influence the adoption of formative assessment is crucial to implement various assessment strategies effectively. Therefore, survey conducted on perceptions of primary school teachers in Riyadh province of Saudi Arabia regarding 14 selected factors. By stratified random sampling, data is gathered from the teachers of 15 schools located in the Riyadh province of Saudi Arabia. 210 fully completed questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…Previous studies on the perception of Saudi teachers on formative assessment necessitate a comparative review of the existing literature. According to Alotaibi (2019), Saudi Arabian teachers treat formative assessment as an unnecessary and counterproductive approach to grading learners. Specifically, the study revealed how Saudi Arabian teachers prefer the implementation of formative assessment as a group activity.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on the perception of Saudi teachers on formative assessment necessitate a comparative review of the existing literature. According to Alotaibi (2019), Saudi Arabian teachers treat formative assessment as an unnecessary and counterproductive approach to grading learners. Specifically, the study revealed how Saudi Arabian teachers prefer the implementation of formative assessment as a group activity.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…A survey by Alotaibi (2019) explored the perception of teachers on specific factors that influence the adoption of formative assessment in Saudi Arabian schools. In particular, the study focused on 14 factors that influence the perception of teachers working within Riyadh province of Saudi Arabia.…”
Section: Teachers' Perspective In Saudi Arabiamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the summative assessment has to do with the formal evaluation aims at measuring how much learners know and decides the learners' completion of the course, Tessmer (1993;1994), O'Malley and Pierce ( 1996), Spafford, Pesce, and Grosser (1998), Black and Wiliam (1998), Boston (2002), Yorke (2003), Chappuis, Stiggins, Arter, and Chappuis (2004), Race (2009), Cauley and McMillan (2010). Recent and related studies in the Saudi EFL context have been done which confirmed the importance of and the advantages of formative assessment though such type of assessment not implemented more in Saudi classes, Kariri, Cobern and Bentz (2018), Alotaibi (2019).…”
Section: Formative and Summative Assessmentsmentioning
confidence: 90%
“…Today, in order to have a fully effective teaching / learning process, the assessments need to include observation, perception, decision, and action when identifying prospects as the main goal. In this permanent process, it is not the final academic outcome that is of primary importance but rather the learning process itself, its reflection, deep consideration, and feedback to all participants of the educational process (Alotaibi, 2018). The result is the learner's personal and authentic progress.…”
Section: Introductionmentioning
confidence: 99%